Commodity and Manufactures Prices in the Long Run - Boughton, James (IMF Working Papers; Working Paper ;, 1991)
The low level of primary commodity prices since 1985 is examined in the context of the behavior of those prices relative to prices of manufactured goods since 1854. The Prebisch-Singer hypothesis of a secular decline in relative commodity prices is sustained, but the recent decline is shown to be well outside the realm of historical experience. Commodity and manufactures prices are found to be cointegrated, conditional on the negative trend and a number of unexplained short-term swings. The earlier finding of a Gibson paradox is explained in terms of the difference between short- and long-run relationships.